The book Cosmos, by Alexander von Humboldt - Heinz, Marion; Hoyos Vásquez, Guillermo (Estudios de Filosofía, 1999)
Given the fragmentarity of the particular sciences developed in the doors of the twentieth century, Cosmos, by Humboldt, is an interesting work because: 1) it sums up the diverse and new knowledge at that time, and 2) it intends to define the place of humans in the Cosmos. lt is imperative to read Humboldt over in order to know his attitude towards the dispersion of knowledge that forbids one to get an idea of the meaning of the whole. In the first part the thesis is that such conception inscribes itself in the scientific paradigm buílt up by the so called neovitalism. The second part emphasizes, then, the relation between nature and spirit.